Formation and Function of Mammalian Epithelia: Roles for Mechanosensitive PIEZO1 Ion Channels - Stewart, Teneale A.; Davis, Felicity M. (Frontiers in Cell and Developmental Biology, 2019)
Mechanical forces play important roles in shaping mammalian development. In the embryo, cells experience force both during the formation of the mammalian body plan and in the ensuing phase of organogenesis. Physical forces – including fluid flow, compression, radial pressure, contraction, and osmotic pressure – continue to play central roles as organs mature, function, and ultimately dysfunction. Multiple mechanisms exist to receive, transduce, and transmit mechanical forces in mammalian epithelial tissues and to integrate these cues, which can both fluctuate and coincide, with local and systemic chemical signals. Drawing near a decade since the discovery of the bona fide mechanically activated ion channel, PIEZO1, we discuss in this mini-review established and emerging roles for this protein in the form and function of mammalian epithelia.